2020
DOI: 10.3390/nano10040608
|View full text |Cite
|
Sign up to set email alerts
|

Two-Phase Equilibrium Conditions in Nanopores

Abstract: It is known that thermodynamic properties of a system change upon confinement. To know how, is important for modelling of porous media. We propose to use Hill’s systematic thermodynamic analysis of confined systems to describe two-phase equilibrium in a nanopore. The integral pressure, as defined by the compression energy of a small volume, is then central. We show that the integral pressure is constant along a slit pore with a liquid and vapor in equilibrium, when Young and Young–Laplace’s laws apply. The int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 34 publications
3
46
0
Order By: Relevance
“…It has been shown that the physical properties of liquids in confinement such as the pressure, density, viscosity and diffusivity can spatially vary (i.e. evidence of localised phenomena) [151][152][153][154][155][156][157][158][159][160][161]. These local effects typically subside within a couple of molecular diameters away from the walls [162][163][164][165].…”
Section: Finite-size Dependence Of Self-diffusivities Of Fluids In Comentioning
confidence: 99%
“…It has been shown that the physical properties of liquids in confinement such as the pressure, density, viscosity and diffusivity can spatially vary (i.e. evidence of localised phenomena) [151][152][153][154][155][156][157][158][159][160][161]. These local effects typically subside within a couple of molecular diameters away from the walls [162][163][164][165].…”
Section: Finite-size Dependence Of Self-diffusivities Of Fluids In Comentioning
confidence: 99%
“…It is The subdivision potential is defined here as the increase in the total internal energy as the number of slit pores increases while keeping , and constant. This definition is different from the definition in a previous article by us [ 23 ], where only the entropy, volume and number of particles were kept constant and not the surface area. This led to a different expression for the subdivision potential.…”
Section: Theorymentioning
confidence: 86%
“…The approach following Gibbs is most popular [ 15 , 16 , 17 , 18 , 19 ]. However, the method of Hill may offer an attractive alternative [ 20 , 21 , 22 , 23 , 24 , 25 ], partly because it may provide an independent check on Gibbs procedure, but also because general geometric scaling relations are obtainable from Hill’s method. We will see that this is also the case in the present study.…”
Section: Introductionmentioning
confidence: 99%
“…This function, which can be viewed as a correction from macroscopic thermodynamics, has been called the subdivision potential, because the process of subdividing the ensemble into a larger number of smaller systems, while keeping , , and constant, requires the energy . It has recently been shown to contain interesting size-scaling laws [ 15 , 19 , 20 ]. The replica energy, the subdivision potential and the scaling laws are particular for the variables that control the ensemble.…”
Section: Nanothermodynamic Frameworkmentioning
confidence: 99%